Inteligencia emocional y estrategias de afrontamiento al estrés en enfermeras (os) del Hospital Regional Docente De Trujillo - Castillo Morillo, Rocío Thamar (2019)
This research descriptive, correlational / causal, with quantitative approach was conducted in the service of Surgery "A" and "B" of the Regional Hospital of Trujillo, in order to investigate the relationship between the level of emotional intelligence and types of stress coping strategies in the Nurses (os); "Emotional Intelligence Inventory On Ice Bar: - A Na" and "Coping Strategies Inventory Stress - Ciss" for collecting data two instruments were used. The sample consisted of 24 nurses (os). For statistical analysis the IBM SPSS STATISTIC version 23. In analyzing the results it was found that 95.8 percent of nurses (I) presented average level of emotional intelligence and 4.2 percent from a low level of emotional intelligence was used well same 91.7 percent of nurses (I) had a stress coping focused on the problem, and 8.3 percent presented an avoidant coping with stress. Given these results we conclude that there is a highly significant relationship (p = 0.00) between the level of emotional intelligence and types of stress coping strategies